Inclusão intelectual no ensino regular: perímetros e áreas de regiões poligonais - COLLAREDA, Susana Michelim (2020)
This paper discusses the performance of geometric activities, involving perimeter and area of polygons: square, rectangle and right triangle, using manipulative materials with three students with intellectual disability disorder in different degrees. The activities were developed in the school environment in which the performance and conceptual understanding of the activities were observed and how they reacted when submitted to tasks that inferred the development of their motor, intellectual and social skills using concrete materials as a pedagogical method. Given the paradigm of the inclusion of students with special needs in the schools of the municipal and state public network, a need arose to realize the learning of these students. Thus, a pedagogical didactic survey was made, especially in Vygotski's theories, which could base theories and practices that stimulate the ludic of these students with intellectual development disorder, making the teaching and learning process something more accessible and pleasant to them. All research was conceptualized qualitatively, seeking to answer the following question: “What are the possible contributions of a proposal to use manipulative materials for the teaching of perimeters and areas of the polygonal regions: square, rectangle and triangle rectangle, for 9th grade students Fundamental with intellectual disability? ”The concrete manipulative materials helped in the development of playfulness and played an important role in the present project, through them it was possible to observe how students with intellectual disabilities improved their knowledge and how this knowledge could be part of their daily lives. The insertion of manipulative materials in the process of knowledge construction provided significant changes in the learning of individuals with special needs studied in this research, such as: understanding and using the perimeter in other areas of knowledge such as art; resignify the mediating relationship of the wisest colleagues, valuing their help; recognizing in the material forms and methods used in everyday life. These materials could facilitate the comprehension of the contents addressed providing a playful way for learning, favored the mediator intervention of the teacher.